Serial lumbar and ventricle cerebrospinal fluid lactate dehydrogenase activities in patients with leptomeningeal metastases from solid and haematological tumours. Issue 3 (March 1987) - Twijnstra, A; van Zanten, A P; Hart, A A; Ongerboer de Visser, B W
Abstract : Lactate dehydrogenase (LDH) activities were measured in cerebrospinal fluid in 350 patients with various neurological diseases to establish the sensitivity and specificity of the CSF LDH as a marker for the diagnosis of leptomeningeal metastases. Slight elevations of CSF LDH were observed in nonmalignant diseases, while marked elevations were observed in a considerable number of patients with bacterial meningitis. A sensitivity of 79% and a specificity of 83% were calculated. In the 34 patients with leptomeningeal metastases from solid and haematological tumours, the LDH in lumbar and ventricular CSF were measured simultaneously. The lumbar CSF LDH concentration in patients with leptomeningeal metastases was about five times greater than that in the ventricular CSF. No relationship was found between the CSF LDH and histology of the primary tumour. A good correlation was demonstrated between the lumbar CSF LDH and the effected area of the neuraxis. Serial determinations of CSF LDH showed a relationship between level changes and responses to therapy or progression. The findings of this study indicate that measurement of LDH in CSF can be used as an adjunctive diagnostic test for leptomeningeal metastases and in monitoring the efficacy of treatment.